Self-esteem among nursing students at a public university in Saudi Arabia: A cross-sectional study - Ahmed Mansour Almansour (Belitung Nursing Journal, 2023)
Background: Self-esteem is a subjective assessment of one’s own value and worth as a person. Self-esteem is recognized as an indicator of a person’s mental health, with lower levels associated with mental conditions such as stress and depression. In the context of nursing education, self-esteem has been linked to student’s academic performance, clinical competence, and overall well-being. Existing literature suggests that self-esteem among student nurses varies across countries and cultures. Assessing the self-esteem level among student nurses is essential for identifying students at risk of experiencing academic difficulties or mental health problems. Objective: The study aimed to assess the self-esteem level among student nurses at Al-Majmaah University, Saudi Arabia. Methods: A cross-sectional design was employed and conducted with 346 nursing students conveniently selected at Majmaah University in Saudi Arabia in May 2023. A self-reported questionnaire utilizing the Rosenberg Self-Esteem Scale (RSES) was employed. Data were analyzed using SPSS Statistics software, including descriptive and inferential statistical techniques. Results: The findings revealed that 265 students (76.6%) had moderate self-esteem levels, 53 students (15.3%) had low self-esteem, and 28 students (8.1%) had high levels of self-esteem. Examination of self-esteem in relation to socio-demographic variables resulted in statistically significant correlations with the year of study, physical health, psychological health, and father’s education (p <0.05). Conclusion: The study’s results offer valuable insights for nurse educators, which can serve as a compass for designing educational and awareness programs to boost self-esteem among student nurses. These initiatives hold significance in equipping students with the necessary attributes for their upcoming roles as professional nurses. Nonetheless, further investigations are warranted to delve into self-esteem and associated factors.